Sweet Corn Growth and Yield Response through Potassium under Drought Stress - Rosa, Angela Griya Adinda; Udayana, Cicik; Hariyono, Didik (Agro Bali : Agricultural Journal, 2025)
Sweet corn is recognized as one of the plants with relatively high economic value and potential for expansion, increasing from 8.31 to 18 million tons. Arranging planting distance and applying potassium when conditions are stressed by drought can be one of the efforts to modify the environment for plant growth.  This study employed a split-plot design repeated three times, consisting of a main plot and three levels of sub-plots. The main plot is J1 = 75 x 20 cm, J2 = 50 x 30 cm, and J3 = 60 x 25 cm. While the sub-plots are K1 = 100 kg.ha-1, K2 = 200 kg.ha-1, dan K3 = 300 kg.ha-1. The results obtained show that the arrangement of closer planting distances between rows 60 x 25 cm with increasing doses of Potassium 200 kg.ha-1 results in an interaction with increased growth and optimal sweet corn yields. The microclimate conditions of sweet corn, including soil moisture, were influenced by spacing and potassium dosage. The relationship between plant distance and potassium dosage to soil moisture is directly proportional or linear. Plant distance of 60 x 25 cm with increasing potassium dose, such as at a potassium dose of 300 kg.ha-1 produces the most moist soil moisture under drought stress conditions.